PENERAPAN MODEL KEPEMIMPINAN ROSULI PADA PROGRAM STUDI PENDIDIKAN AGAMA ISLAM FAKULTAS TARBIYAH DAN ILMU KEGURUAN INSTITUT AGAMA ISLAM NEGERI PONTIANAK TAHUN 2014-2017 - Ma’ruf Ma’ruf; Surianto Surianto (IAIN Pontianak, 2021)
Abstract: Leadership is one of the most frequently encountered topics and is always interesting to research and study, because leadership is one of the most important factors in playing a role and influencing the good and bad of an institution. There have been many studies that have proven that leaders play an important role in development in achieving institutional goals. Likewise, the leadership in the Islamic Religious Education Study Program at the Tarbiyah Faculty and Teacher Training at the Pontianak Islamic Religious Institute, which is the longest and most interested study program among the study programs at IAIN Pontianak. In the last few years, admission to the Islamic Religious Education Study Program, FTIK IAIN Pontianak, has stuck in just nine classes, so that many applicants have been rejected due to a lack of study rooms and teaching staff. From the beginning the Islamic Religious Education Study Program FTIK IAIN Pontianak was operational until 2017 yesterday, the assessment from BAN PT of its accreditation was still of C and B values. FTIK IAIN Pontianak got an A. The only study program that got an A from several study programs visited. This achievement is inseparable from the leadership model applied to the Islamic Religious Education Study Program of the Faculty of Tarbiyah and Teacher Training at the Pontianak State Islamic Institute, especially in leadership in 2014-2017. The leadership in general is Relationship Oriented leadership, in this case leadership that is collegial collective. in its application using the apostolic leadership model, namely; 1) Integrity and transparency (shiddiq), 2) Accountability (amanah), 3) Participatory communicative (tabligh), and 4) Creative and inspirational (fathanah). Keywords: Model, Leadership, PAI Study Program, 2014-2017